PARENTING STYLES IN DAHL’S DANNY THE CHAMPION OF THE WORLD - Sheva, Aura Duta (PARADIGM: Journal of Language and Literary Studies, 2023)
Baumrind that how parents raise their children affects the children’s behavior. That is because children spend most of their time with their parents. This phenomenon is reflected in Roald Dahl’s children’s novel Danny the Champion of the World, which describes the parenting William gave to Danny. This analysis explores the elements and the effects of parenting styles in Dahl’s Danny the Champion of the World. The present study uses literary criticism, focusing on parenting style. This analysis applies the theory of parenting style proposed by Diana Baumrind. It also reveals that the parenting style elements that William gave to Danny are seven elements: Involvement, Nurturance, Affection, Danny’s Number-One Supporter, Education, A Good Companion, and Demand with Love. Furthermore, the effects of parenting styles on Danny’s behavior are shown the behaviors of Compliance, Openness to Communicate, High Enthusiasm to Learn, and Gratefulness. Thus, the researcher concludes that Dahl’s Danny the Champion of the World provides not only a story about father-and-son relationship but also knowledge about parenting styles and the effect of good parenting styles on a child’s behaviors.